Transformational Leadership of School Principals as a Catalyst for Digital Learning Implementation in Primary Schools - Handayani, Wini; Hidayat, Syarip; Elan, Elan (Papanda Publisher, 2025)
This study explores the role of transformational leadership among principals in effectively implementing digital learning within elementary educational institutions in Indonesia. The urgency of digital transformation in education, especially after the pandemic, highlights the need for leadership to align vision, motivation, and infrastructure to support sustainable pedagogical innovation. The study examines how transformational leadership practices influence the development of digital learning ecosystems at the school level, particularly by fostering teacher empowerment, professional growth, and strategic resource mobilisation. This research systematically identifies, evaluates, and synthesises empirical studies and theoretical frameworks relevant to transformational leadership and digital learning using a literature review methodology. Data were collected through document analysis of peer-reviewed journal articles and academic publications. Following Braun and Clarke’s six-phase model, thematic analysis was employed to identify key patterns and concepts. The results reveal four major themes: (1) the importance of a shared and inspirational vision for digital transformation, (2) leadership strategies to motivate and support teacher-led innovation, (3) the promotion of intellectual stimulation and continuous professional development, and (4) the mobilisation of digital infrastructure and material resources. These findings suggest that transformational leadership fosters a culture of innovation, collaboration, and responsiveness, positioning schools to adapt effectively to technological and educational change. The study concludes that sustained principal commitment, strategic leadership, and supportive conditions are essential for embedding digital learning as a core element of school development.